Effective purification of cold-rolling sludge as iron concentrate powder via a coupled hydrothermal and calcination route: From laboratory-scale to pilot-scale. (10th December 2020) - Zhu, Suiyi; Li, Tong; Wu, Yaqiong; Chen, Yu; Su, Ting; Ri, Kyonghun; Huo, Yang
Abstract: Cold-rolling sludge (CRS), a typical solid waste, is mass produced during strip cleaning and rolling. Given its low Fe concentration, CRS cannot be directly recycled as iron pellet for steel making, and it is commonly solidified before safety landfill. Herein, CRS was purified as commercial iron concentrate powder via a coupled alkaline hydrothermal and calcination route. The sludge contained 45.6 wt% Fe, and its major impurities included 6.2 wt% Al, 13.5 wt% carbon and 9.7 wt% halite. After the hydrothermal treatment, the contents of Al and carbon in the treated sludge decreased to 0.16 and 12.1 wt%, respectively, and halite was almost completely removed. Subsequently, the Fe content in the treated sludge increased to 60.6 wt%, which was higher than that obtained with conventional methods, e.g. direct washing (51.4 wt% Fe), alkaline washing (52.7 wt% Fe), Fenton oxidation (52.4 wt%) and direct calcination (53.7 wt%). The treated sludge was further calcined at 800 °C. The calcined product showed unchanged amounts of Al, carbon content that dropped to 3.5 wt% and Fe that steadily rose to up to 66.1 wt%. These findings enabled the calcined product to be used as a high-grade iron concentrate powder. NaOH concentration, hydrothermal temperature and time were optimised to 8 M, 160 °C and 6 h at the laboratory scale, respectively. The solid–liquid ratio and recycling of supernatant were limited to 1 and 4 at the pilot scale, respectively. Under optimal conditions, the supernatant was reused four times, and the obtained product contained 62.7 wt% Fe, which meets the commercial standard of iron concentrate powder (>60 wt%). This coupled route was considerably effective for recycling CRS as iron concentrate powder and was successfully employed at the pilot scale. Graphical abstract: Image 1 Highlights: Pilot-scale purification of CRS as iron concentrate powder was performed. Impurity removal of 6.1% Al and 11.1% C was achieved by a hydrothermal and calcination route. Four-time reutilisation of hydrothermal supernatant was performed successfully at the pilot scale. Effective purification of Fe content from 45.6 wt% to 66.1 wt% was obtained.